THE IMPORTANT-PERFORMANCE ANALYSIS OF COMPENSATION PROGRAMS AT PT. BANK SULUT TONDANO - Turambi, Valeria (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT One of the important factors of the succession of a company is the employee, and compensation plays an important role on the performance of the employee. The objective of this research is to analyze the importance and the performance of compensation programs in PT. Bank Sulut. 22 employees in PT. Bank Sulut Tondano were surveyed as respondents. The type of this research is descriptive and used important-performance analysis (IPA) as the analytical tool. The result shows the importance of all of the compensation programs in PT. Bank Sulut are highly rated, but the performance of Salary and Employee Welfare are perceived to be low. The performance of Annual Leave and Uniforms has excessive the importance of these programs so the excessive performance have to be reduced by the amount and allocated to programs that has a lack of performance. Bedside the four programs mentioned above, the performance of other programs should be maintained. Keywords: compensation, importance-performance analysis, PT. Bank Sulut